Does food sharing lead to food waste reduction? An experimental analysis to assess challenges and opportunities of a new consumption model. (1st June 2018) - Morone, Piergiuseppe; Falcone, Pasquale Marcello; Imbert, Enrica; Morone, Andrea
Abstract: Food security, along with growing population and the associated environmental concerns, make food waste and loss a central topic in economic analysis. While food losses occur mostly at the production, postharvest and processing phases of the supply chain, food waste takes place mainly at the end of the chain and therefore concerns primarily the habits and behaviour patterns of retailers and consumers. Many solutions and practices have been proposed and oftentimes implemented in order to " keep food out of landfills ", thus reducing food waste at the source. However, little attention has been paid to the possible sharing of consumer-side food surplus. In this context, food sharing could represent an effective way to tackle food waste at the consumers' level, with both environmental and economic potential positive effects. However, there is still little empirical evidence testing the effectiveness of introducing sharing economy approaches to reduce food waste. This study seeks to fill this gap through a framed field experiment. The authors performed two experimental treatments; in the control treatment students were asked to behave according to their regular food consumption habits, and in the food sharing treatment the same students were instructed to purchase food, cook and consume it collectively. Preliminary results showed that the adoption of food sharing practices by households do not automatically translate into food waste reduction. A number of factors, were evident from a quali-quantitative analysis of the sample (i.e. environmentally friendly behaviour, economic awareness, domestic skills and collaborative behaviors ) might act as 'enablers' to make sharing practices more effective. The replication of our study at a larger scale will allow further investigation of the relevance of the identified enablers in order to unlock the full potential of food sharing practices.